Evaluation of anti‐islanding techniques for renewable energy powered distributed generators using analytic network process. Issue 9 (1st October 2016) - Datta, Asim; Saha, Debasree; Ray, Amitava; Das, Priyanath
Abstract : Recent high penetration of renewable energy powered distributed generation (RE‐DG) is imposing new challenges to the anti‐islanding protection. A survey on the existing islanding‐detection techniques (IDTs) reveals that a wide variety of IDTs are available. Thus, it is an anxiety to decide which kind of islanding‐detection method is suitable for a particular RE‐DG application. Therefore, it is of great significance to select an appropriate IDT depending on the application and criteria preference of the end‐users. There can be mutual correlation among the different criteria of anti‐islanding selection. In this research, a decision‐making technique, the analytic network process, is adopted to select an appropriate IDT for a particular RE‐DG application by analysing operational characteristics of different IDTs. Unlike hierarchy‐based approach, the technique considers the interrelationships amongst the attributes of anti‐islanding selection in order to provide the best selection. Finally, the sensitivity analysis is performed to check the robustness of the selection procedure.